Prenatal cardiac biometry and flow assessment in fetuses with bicuspid aortic valve at 20 weeks' gestation: multicenter cohort study. (10th November 2021) - Vedel, C.; Rode, L.; Bundgaard, H.; Iversen, K.; Jørgensen, F. S.; Petersen, O. B.; Sillesen, A.‐S.; Sundberg, K.; Vejlstrup, N.; Zingenberg, H.; Tabor, A.; Ekelund, C. K.
ABSTRACT: Objective: To investigate prenatal changes in cardiac biometric and flow parameters in fetuses with bicuspid aortic valve (BAV) diagnosed neonatally compared with controls with normal cardiac anatomy. Methods: This analysis was conducted as part of the Copenhagen Baby Heart Study, a multicenter cohort study of 25 556 neonates that underwent second‐trimester anomaly scan at 18 + 0 to 22 + 6 weeks' gestation and neonatal echocardiography within 4 weeks after birth, in Copenhagen University Hospital Herlev, Hvidovre Hospital and Rigshospitalet in greater Copenhagen, between April 2016 and October 2018. From February 2017 (Rigshospitalet) and September 2017 (Herlev and Hvidovre hospitals), the protocol for second‐trimester screening of the heart was extended to include evaluation of the four‐chamber view, with assessment of flow across the atrioventricular valves, sagittal view of the aortic arch and midumbilical artery and ductus venosus pulsatility indices. All images were evaluated by two investigators, and cardiac biometric and flow parameters were measured and compared between cases with BAV and controls. All cases with neonatal BAV were assessed by a specialist. Maternal characteristics and first‐ and second‐trimester biomarkers were also compared between the two groups. Results: Fifty‐five infants with BAV and 8316 controls with normal cardiac anatomy were identified during the study period and assessed using the extended prenatal cardiac imaging protocol. There were three times as many mothers who smoked before pregnancy in the group with BAV as in the control group (9.1% vs 2.7%; P  = 0.003). All other baseline characteristics were similar between the two groups. Fetuses with BAV, compared with controls, had a significantly larger diameter of the aorta at the level of the aortic valve (3.1 mm vs 3.0 mm (mean difference, 0.12 mm (95% CI, 0.03–0.21 mm))) and the pulmonary artery at the level of the pulmonary valve (4.1 mm vs 3.9 mm (mean difference, 0.15 mm (95% CI, 0.03–0.28 mm))). Following conversion of the diameter measurements of the aorta and pulmonary artery to Z ‐scores and Bonferroni correction, the differences between the two groups were no longer statistically significant. Pregnancy‐associated plasma protein‐A (PAPP‐A) multiples of the median (MoM) was significantly lower in the BAV group than in the control group (0.85 vs 1.03; P  = 0.04). Conclusions: Our findings suggest that fetuses with BAV may have a larger aortic diameter at the level of the aortic valve, measured in the left‐ventricular‐outflow‐tract view, and a larger pulmonary artery diameter at the level of the pulmonary valve, measured in the three‐vessel view, at 20 weeks' gestation. Moreover, we found an association of maternal smoking and low PAPP‐A MoM with BAV. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.